2021
DOI: 10.1002/smll.202006111
|View full text |Cite
|
Sign up to set email alerts
|

Pb‐Doped Ag2Se Quantum Dots with Enhanced Photoluminescence in the NIR‐II Window

Abstract: Ag2Se quantum dots (QDs) as an effective biological probe in the second near‐infrared window (NIR‐II, 1000–1700 nm) have been widely applied in bioimaging with high tissue penetration depth and high spatiotemporal resolution. However, the ions deficiency and crystal defects caused by the high Ag+ mobility in Ag2Se crystals are mainly responsible for the inefficient photoluminescence (PL) of Ag2Se QDs. Herein, a tailored route is reported to achieve controllable doping of Ag2Se QDs in which Ag is exchanged by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Although HgTe remains the dominant CQD infrared material for wavelengths longer than 3 μm, HgSe and HgS were also investigated as potential candidates, opening up the possibility for intraband transitions in infrared detectors. , These transitions can only be observed when electrons from external or self-dopants are stabilized in the conduction band at specific energies that avoid reaction with the environment but can still enable higher temperature operation with reduced Auger recombination rates. , Including HgSe and HgS quantum dots, most photoactive intraband materials overcome the challenge of stabilizing an electron in the 1S e state, capable of an optical transition to the 1P e state that is smaller in magnitude compared to the interband gap (band gap). Utilizing intraband transitions in materials with wider band gaps can open the opportunity to use environmentally friendly materials to replace common narrow band gap semiconductors, which typically comprise heavy metals. , Neither Hg nor Pb is compliant with the Restriction of Hazardous Substances (RoHS) and pose severe health and environmental risks if improperly handled, stored, or disposed . While Hg and Pb chalcogenides are still being developed toward commercialization, Ag 2 Se has thoroughly been investigated as a heavy metal free alternative NIR and MWIR-active material. ,, Additionally, a cytotoxicity study on Ag 2 Se concluded that Ag 2 Se is a much less toxic material, allowing large-scale MWIR detector implementation or NIR biomarker use in the human body. , Currently, Ag 2 Se lags behind its Pb and Hg counterparts in performance metrics of infrared detectors, but there has been significant progress in the past 3 years. For example, recently reported Ag 2 Se MWIR devices have shown rapid progress, a 70-fold increase in responsivity from 0.3 to 21 mA/W within 1 year. , The improved responsivity is promising, but while bearing an uncanny resemblance to HgSe CQDs in terms of IR absorption, the performance of Ag 2 Se CQD detectors is orders of magnitude lower than their HgSe counterpart .…”
Section: Introductionmentioning
confidence: 99%
“…Although HgTe remains the dominant CQD infrared material for wavelengths longer than 3 μm, HgSe and HgS were also investigated as potential candidates, opening up the possibility for intraband transitions in infrared detectors. , These transitions can only be observed when electrons from external or self-dopants are stabilized in the conduction band at specific energies that avoid reaction with the environment but can still enable higher temperature operation with reduced Auger recombination rates. , Including HgSe and HgS quantum dots, most photoactive intraband materials overcome the challenge of stabilizing an electron in the 1S e state, capable of an optical transition to the 1P e state that is smaller in magnitude compared to the interband gap (band gap). Utilizing intraband transitions in materials with wider band gaps can open the opportunity to use environmentally friendly materials to replace common narrow band gap semiconductors, which typically comprise heavy metals. , Neither Hg nor Pb is compliant with the Restriction of Hazardous Substances (RoHS) and pose severe health and environmental risks if improperly handled, stored, or disposed . While Hg and Pb chalcogenides are still being developed toward commercialization, Ag 2 Se has thoroughly been investigated as a heavy metal free alternative NIR and MWIR-active material. ,, Additionally, a cytotoxicity study on Ag 2 Se concluded that Ag 2 Se is a much less toxic material, allowing large-scale MWIR detector implementation or NIR biomarker use in the human body. , Currently, Ag 2 Se lags behind its Pb and Hg counterparts in performance metrics of infrared detectors, but there has been significant progress in the past 3 years. For example, recently reported Ag 2 Se MWIR devices have shown rapid progress, a 70-fold increase in responsivity from 0.3 to 21 mA/W within 1 year. , The improved responsivity is promising, but while bearing an uncanny resemblance to HgSe CQDs in terms of IR absorption, the performance of Ag 2 Se CQD detectors is orders of magnitude lower than their HgSe counterpart .…”
Section: Introductionmentioning
confidence: 99%
“…[14,24,64,65] Both syntheses of NIR-II emitting SNCs and studies of their optical properties have achieved considerable progress in the past decade. Representative materials mainly include binary silver chalcogenides such as Ag 2 S, [66][67][68] Ag 2 Se, [69][70][71] and Ag 2 Te, [72][73][74] III-V SNCs (e.g., InAs, InSb), [75][76][77][78][79] and ternary copper (silver) indium chalcogenide-based SNCs. [35,51,54,80,81] The synthetic strategies of representative NIR-II SNCs and their optical properties are summarized in Table 1.…”
Section: Synthesis and Optical Properties Of Nir-ii Emitting Sncsmentioning
confidence: 99%
“…For instance, Ag 2 Se SNCs coupled with gadopentetic acid (Gd-DTPA), clinically approved MRI contrast agent, could be used for PL as well as MR imaging, 75 whereas Cu + -doped Ag 2 S SNCs can achieve NIR PL and PA imaging, as well PTT. 76 The presence of Cu + in Ag 81 However, without falling back onto using toxic heavy metals, H. Yang, have made alloyed AgAuSe SNCs with emission tunable in the 820-1170 nm range and PLQY up to 65.3 %. 82 And most recently, the Au-doped Ag 2 Te SNCs, have been applied to study and diagnose ischemia.…”
Section: Ag-based Sncsmentioning
confidence: 99%